Making Choices: What Readers Say About Choosing Books to Read for Pleasure - Ross, Catherine Sheldrick (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
this paper analyses 194 open-ended interviews with committed readers who read for pleasure, focusing in particular on interviewees' responses to questions about how they choose and how the reject a book. The analysis suggests that a comprehensive model for the process of choosing books for pleasure-reading must include five related elements that are examined in the paper. . .